Performance Appraisal and Job Satisfaction for Workers Without and With Disabilities by Gender - Pagan, Ricardo; Malo, Miguel Ángel (Social indicators research, 2021)
This study analyses the effects of performance appraisal on the levels of job satisfaction reported by workers without and with disabilities (aged 16–64) by gender. Particularly, we are interested in investigating the impact of monetary rewards such as pay, bonuses, future raises and potential promotion on job satisfaction by disability status and checking differences by gender. Our data come from the German Socio-Economic Panel (SOEP) for the years 2004, 2008, 2011 and 2016. We estimate job satisfaction equations running a fixed effect "Probit Adapted OLS" model. We find that males with disabilities are less likely to be satisfied with their jobs when they are subject to performance appraisal with monetary effects (appraisals with both short and long-term rewards explain this result), whereas the opposite result is found for females with disabilities (in the case of receiving long-term rewards). We estimate the association of these performance appraisal schemes with recognition from superiors, and with their efforts, personal advances and pay, and we find a coherent pattern with previous results.